2019
DOI: 10.3390/ijms20020356
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Assembly of LPS, Its Structural Alterations and Cellular Response to LPS Defects

Abstract: Distinguishing feature of the outer membrane (OM) of Gram-negative bacteria is its asymmetry due to the presence of lipopolysaccharide (LPS) in the outer leaflet of the OM and phospholipids in the inner leaflet. Recent studies have revealed the existence of regulatory controls that ensure a balanced biosynthesis of LPS and phospholipids, both of which are essential for bacterial viability. LPS provides the essential permeability barrier function and act as a major virulence determinant. In Escherichia coli, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
128
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 86 publications
2
128
0
Order By: Relevance
“…Our results also highlight that phage infectivity depends on the host cellular physiology and, in particular, membrane characteristics of the host imparted by LPS and outer membrane protein biogenesis pathways [108,109,203]. For instance, our results indicate that the disruptions in LPS (for example, deletions or downregulation of waa genes Fig.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Our results also highlight that phage infectivity depends on the host cellular physiology and, in particular, membrane characteristics of the host imparted by LPS and outer membrane protein biogenesis pathways [108,109,203]. For instance, our results indicate that the disruptions in LPS (for example, deletions or downregulation of waa genes Fig.…”
Section: Discussionsupporting
confidence: 53%
“…We also observed higher fitness scores for a number of genes involved in LPS biosynthesis (waaC, waaD, waaE, waaF, lpcA) in the presence of T4, LZ4 and λ phages when grown on solid plates. These results suggest that LPS components either play an important role in efficient phage infection cycle or these LPS truncations lead to a destabilized membrane and probably decrease outer membrane protein levels via envelope stress response [101,[106][107][108][109]. A detailed description about many of the genes we identified in this study is included as a Supplemental Note.…”
Section: Rb-tnseq Identifies Known Receptors and Host Factors For Allmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown that deletion of yciM is tolerated in E. coli lacking lpp (13,16). It is thought that deletion of lpp restores OM lipid balance in the yciM mutant by increasing the number of acyl chains available for PL biosynthesis (16,20). As seen in (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…It has previously been shown that deletion of the highly abundant lipoprotein Lpp, which tethers the OM to the underlying peptidoglycan, can suppress deletion of yciM (13,(16)(17)(18). As Lpp is anchored to the OM by three acyl chains (19), it has been hypothesized that loss of lpp restores lipid balance in the ΔyciM mutant by increasing the number of acyl chains available for PL biosynthesis (16,20).…”
mentioning
confidence: 99%